PENGARUH MOTIVASI KONSUMEN TERHADAP PERILAKU BRAND SWITCHING PADA PRODUK SEPEDA MOTOR YAMAHA KE SEPEDA MOTOR HONDA DI KOTA MEDAN - Zebua, Viktor Robinson Putra; Sianturi, Charles M; Simangunsong , Ridhon MB (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Consumer dissatisfaction can also be a driving factor for Brand Switching. Dissatisfaction occurs as a consumer response to the evaluation of the perceived discrepancy between initial expectations before purchase and the actual performance of the product that is perceived after using the product in question. This research aims to determine the influence of motivation on brand switching behavior for Yamaha motorbike products to Honda motorbikes in the city of Medan. In this research, researchers used quantitative research. The number of samples that will be used in this research is 96 respondents who previously used Yamaha motorbike products and then switched to Honda motorbikes. This research uses simple regression analysis with data processing using SPSS 24 For Windows software. Based on the data processing results above, it can be seen that the t test results for the motivation variable (X) show a tcount value of 10.875 and a significance value of 0.000. Thus tcount>ttable (10.875>1.66) and the significance value at the α = 5% level is 0.000<0.05. So based on the partial hypothesis testing criteria, the first hypothesis is accepted, which means there is a positive and significant influence between motivation (X) on Brand Switching (Y).